TINGKAT KEPUASAN TERHADAP KUALITAS PELAYANAN PEMELIHARAAN DATA PENDAFTARAN TANAH DI KANTOR PERTANAHAN KABUPATEN BOGOR - Gawil Despriyatmoko; Rizal Syarief; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2016)
In order to support bureaucratic reform program in the field of land services, the National Land Registry Agency issued regulations on service standards and decisions about Sapta Land Code. This study aims to analyze the levels of interest and performance of the officials of Land Registry Office in Bogor Regency and to analyze the level of satisfaction of the community on the service of the maintenance of land registry data by the Office. The analytical tool used to determine the satisfaction of the community was the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results showed that there is a gap between the petition of certification and completion of the certificate. The analysis results of IPA based on the dimensions of service quality maintenance of land registry data showed that overall the community is satisfied with the service quality of the Land Registry Office of Bogor Regency. This is demonstrated by the discrepancies between the performance average score of 3,54 and the interest average score of 3,49. Thus, the average score of a positive gap of 0,05 was obtained, and CSI value obtained was 71,14%. Based on the measurement of scale range using the Simamora formula, the CSI analytical results showed that the community is satisfied with the maintenance service of land records in the Land Registry Office of Bogor Regency.Keywords: satisfaction, service quality, maintenance of land registry data, IPA, CSI